Alternative Splicing Regulation of an Alzheimer’s Risk Variant in CLU - Seonggyun Han (International Journal of Molecular Sciences, 2020)
Clusterin (CLU) is one of the risk genes most associated with late onset Alzheimer’s disease (AD), and several genetic variants in CLU are associated with AD risk. However, the functional role of known AD risk genetic variants in CLU has been little explored. We investigated the effect of an AD risk variant (rs7982) in the 5th exon of CLU on alternative splicing by using an integrative approach of brain-tissue-based RNA-Seq and whole genome sequencing data from Accelerating Medicines Partnership—Alzheimer’s Disease (AMP-AD). RNA-Seq data were generated from three regions in the temporal lobe of the brain—the temporal cortex, superior temporal gyrus, and parahippocampal gyrus. The rs7982 was significantly associated with intron retention (IR) of the 5th exon of CLU; as the number of alternative alleles (G) increased, the IR rates decreased more significantly in females than in males. Our results suggest a sex-dependent role of rs7982 in AD pathogenesis via splicing regulation.